2013
DOI: 10.1111/jpc.12266
|View full text |Cite
|
Sign up to set email alerts
|

Influenza infection in infants aged <6 months during the H1N1‐09 pandemic: A hospital‐based case series

Abstract: These novel data are clinically important. Rates of influenza in infants may be reduced by vaccinating close contacts and minimising exposure to infected contacts and cigarette smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…More recently, it has been shown that children under 6 months of age usually only develop a fever but are very likely to be hospitalized with a favorable outcome in most cases, as described by Bender et al 13 Most published articles insist and conclude that influenza rates in infants can be reduced by adopting a cocoon strategy that involves vaccinating close contacts and mothers during pregnancy and even during lactation for those not previously vaccinated. [14][15][16][17][18][19][20][21] It is necessary to promote and stimulate vaccination in all pregnant women, 22 which, in Spain, barely reaches 50% coverage in the best scenario. López-Medina et al 23 showed that during the 2009 pandemic, most Spanish newborns developed a community-acquired influenza infection, which was found to be associated with hospital admissions and favorable short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that children under 6 months of age usually only develop a fever but are very likely to be hospitalized with a favorable outcome in most cases, as described by Bender et al 13 Most published articles insist and conclude that influenza rates in infants can be reduced by adopting a cocoon strategy that involves vaccinating close contacts and mothers during pregnancy and even during lactation for those not previously vaccinated. [14][15][16][17][18][19][20][21] It is necessary to promote and stimulate vaccination in all pregnant women, 22 which, in Spain, barely reaches 50% coverage in the best scenario. López-Medina et al 23 showed that during the 2009 pandemic, most Spanish newborns developed a community-acquired influenza infection, which was found to be associated with hospital admissions and favorable short-term results.…”
Section: Discussionmentioning
confidence: 99%